2016
DOI: 10.1016/j.hpb.2016.03.363
|View full text |Cite
|
Sign up to set email alerts
|

The right hepatic artery syndrome – a rare cause of biliary obstruction

Abstract: showed significantly higher complication rate (n = 20, 36.4% vs. n = 19, 27.1%, p = 0.007), especially intraabdominal fluid collection (n = 6, 10.9% vs. n = 1, 1.4%), and wound infection (n = 6, 10.9% vs. n = 2, 2.9%). AAF group showed lower incidence of postoperative ileus (n = 3, 5.5% vs. n = 11, 15.7%) with statistically marginal significance (p = 0.090). Conclusions: Well-designed randomized controlled trials of anti-adhesive product will be needed for evaluation of effect on postoperative ileus after maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The magnetic resonance cholangiopancreatography findings of the patient also depicted a distended gall bladder and cholangitis was also present. [11]. In our case, the patient had a combined Mirrizi and RHAS the patient underwent laparoscopic cholecystectomy with meticulous dissection of the biliary tree.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The magnetic resonance cholangiopancreatography findings of the patient also depicted a distended gall bladder and cholangitis was also present. [11]. In our case, the patient had a combined Mirrizi and RHAS the patient underwent laparoscopic cholecystectomy with meticulous dissection of the biliary tree.…”
Section: Discussionmentioning
confidence: 79%
“…Stojanovic et al reported a case of biliary obstruction mimicking the klatskin tumor based on a CT scan. Intraoperatively, a cholangiogram was done, and the diagnosis of RHAS was established the patient underwent cholecystectomy with careful delineation of the biliary anatomy the patient was discharged in good condition [ 11 ]. In our case, the patient had a combined Mirrizi and RHAS the patient underwent laparoscopic cholecystectomy with meticulous dissection of the biliary tree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation